Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Kementerian Kesehatan: The Effect of Compensation and Work Motivation on the Performance of Ministry of Health Employees - Putri Maulidia Harom; Frida Aprillia; Sonny Fransisco Siboro (CV Warnak Johanna Nusantara, 2026)
Employee performance is a crucial aspect in determining the success of a government agency, including the Ministry of Health. However, challenges such as employees feeling that compensation is not commensurate with their workload and lack of appreciation for employees are still frequently encountered. This study aims to analyze the effect of compensation and work motivation on employee performance at the Secretariat of the Directorate General of Primary and Community Health. The approach used is quantitative statistics with observation and survey methods through the distribution of questionnaires to the entire population of 40 respondents, using a saturated sampling technique. Data were analyzed with the help of IBM SPSS version 23. The results showed that compensation has a positive and significant effect on employee performance, with a calculated t value of 6.008 > 2.026 and a significance of 0.000 < 0.05. Work motivation has a positive and significant effect on employee performance, with a calculated t value of 11.625 > 2.026 and a significance of 0.000 < 0.05. Simultaneously, both variables showed a significant positive influence on employee performance with a calculated F value of 66.796 > 3.25 and a significance of 0.000 < 0.05.